2020
DOI: 10.1101/2020.03.07.982082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and function of virion RNA polymerase of crAss-like phage

Abstract: 25CrAss-like phages are a recently described family-level group of viruses that includes the most 26 abundant virus in the human gut 1,2 . Genomes of all crAss-like phages encode a large virion-27 packaged protein 2,3 that contains a DFDxD sequence motif, which forms the catalytic site in 28 cellular multisubunit RNA polymerases (RNAPs) 4 . Using Cellulophaga baltica crAss-like phage 29 phi14:2 as a model system, we show that this protein is a novel DNA-dependent RNAP that is 30 translocated into the host cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…1a) [27,35]. Unexpectedly, the eRdRPs appear to be most closely related to a particular group of bacteriophage single subunit 2xDPBB RNAPs [27,36]. The two large RNAP subunits are also fused in linear cytoplasmic plasmids from plants and fungi [37], suggesting that such fusions occur repeatedly in the course of RNAP evolution.…”
Section: Homologies Among Dna and Rna Polymerasesmentioning
confidence: 99%
“…1a) [27,35]. Unexpectedly, the eRdRPs appear to be most closely related to a particular group of bacteriophage single subunit 2xDPBB RNAPs [27,36]. The two large RNAP subunits are also fused in linear cytoplasmic plasmids from plants and fungi [37], suggesting that such fusions occur repeatedly in the course of RNAP evolution.…”
Section: Homologies Among Dna and Rna Polymerasesmentioning
confidence: 99%
“…The predicted products of these genes include a transcriptional regulator, two conserved domain proteins with unknown function and a TROVE domain protein (possible ribonucleoprotein component). A recent study in a distantly related marine crAss-like phage Φ14:2 infecting Cellulophaga baltica indicated that a similarly organised operon of early genes is transcribed by a giant virion-associated multi-subunit RNA polymerase [RNAP, (Drobysheva et al, 2020)], ejected into the cell in the course of infection (Holmfeldt et al, 2013). A homologue of this giant polymerase is present in all crAss-like phages and is also encoded by three large ORFs located in the central part of ΦcrAss001 genome (Guerin et al, 2018;Shkoporov et al, 2018;Yutin et al, 2018).…”
Section: Delayed Release Of φCrass001 Progeny Leads To Multiple Echo mentioning
confidence: 99%
“…Proteomic analysis of the crAss001 virion also indicated the presence of the subunits of the giant polymerase in the assembled phage particle (Shkoporov et al, 2018). Transcription of the middle and late genes is initiated between 10-30 and 30-60 minutes, respectively, and is likely to depend on the action of the host RNAP [as suggested for Φ14:2 in (Drobysheva et al, 2020)]. The middle genes are largely composed of functions associated with DNA replication and recombination, as well as nucleotide metabolism.…”
Section: Delayed Release Of φCrass001 Progeny Leads To Multiple Echo mentioning
confidence: 99%
“…The predicted RNAPs of crAss-like phages are extremely divergent in sequence from all known RNAPs and from each other, suggestive of unusually high evolutionary rates. The recent structural and functional study of the RNAP of Cellulophaga baltica phage phi 14:2 of confirms the involvement of this large protein in the transcription of the phage early genes and shows that it contains two double-psi beta-barrel (DPBB) domains within a single polypeptide, unlike cellular RNAPs in which the two DPBB domains belong to the two largest subunits 12 .…”
Section: Conserved and Group-specific Genomic Features In The Extendementioning
confidence: 84%
“…The gene complements of the crAss-like phages shows a number of distinct features, in particular, a predicted complex transcription machinery centered around an RNA polymerase (RNAP) with an unusual strtucture related to the structure of eukaryotic RNA-dependent RNA polymerases involved in RNA inteference. Recently, the prediction of this unique RNAP has been validated by structural and functional analysis 12 . A phylogenomic analysis of 250 genomes of crAss-like phages led to the proposal of 4 distinct subfamilies and 10 genera 13 .…”
Section: Introductionmentioning
confidence: 99%